Influences of play and gender on transitional writing development - Gausman, Lynsey (My University, 2013)
Can a child sit down, pick up a pencil, and start writing? Have you ever met a child who says, ?I don?t know what to write about?? Writing is a skill that takes time to develop, a skill that a child can grasp when given the opportunity and support. Teachers need to help children develop basic writing skills and also help children give meaning to their writing. Research shows that play gives children experience, builds cognitive development, grows social skills, and can set the foundations for further learning. Research also reveals that if teachers help children develop basic writing skills through mini-lessons and support children by helping them give meaning to their writing, a child can experience success with writing. Play can give children meaning and ideas to bring to their writing. It can spark a child?s creativity and inspire them to pick up that pencil and start writing. This action research project examines children at play and studies if play and/or gender influence the quality and quantity of writing of a transitional writer. Twenty-one children (ten male, eleven female) in first grade participated in a four-week study. Six of twenty-one children (three male, three female) were chosen to be part of a focus group. These six children have an array of writing abilities (two high, two medium, two low, one male and female in each writing ability). Before starting the research, four prewriting pieces were collected from each child giving a baseline before play was introduced into his or her writing. For four weeks, every Tuesday and Thursday, during the children?s writing block, the children wrote for ten to fifteen minutes after coming in from recess. During this time children were given a choice about what they could write about. The writings from Tuesday and Thursday were collected and the six children?s writings were analyzed by using a rubric to look at the quality and quantity of their writing. Pre-and post-writing attitude surveys were used to give the researcher an understanding of how the children felt about writing. A checklist was also used to measure children?s engagement. Eight pieces of writing were collected to analyze the progress of the six focus children. Throughout this study the qualitative and quantitative data collected from the children demonstrates their attitudes towards writing, engagement in the writing process, and shows changes in their quality, quantity, neatness, punctuation and spelling in their writing with play being introduced before their writing block.
Plan B Paper. 2013. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 35 leaves. Includes bibliographical references (leaves 34-35).
Keywords: Play; English language--Composition and exercises--Study and teaching (Elementary); Children--Writing